Genetic parameters and breeding values for daily milk production of Holstein cows in terms of heat stress - Vučković, Goran, agronom; Bobić, Tina; Mijić, Pero, agronom; Gavran, Mirna; Gregić, Maja; Potočnik, Klemen; Bogdanović, Vladan; Gantner, Vesna (2020)
In order to estimate the variance components as well as the breeding value for daily milk production of Holstein cows in terms of heat stress defined as different THI threshold values (68, 70, and 72) 1,275,713 test-day records from 90,159 cows were used. Temperature-humidity index (THI) calculated from ambient temperature and relative humidity recorded in the barns on the milk recording day was used as the measure of heat stress. Daily milk production was analysed as a bivariate variable, in the normal conditions (under the set THIthreshold value), and in terms of heat stress (above the set THIthreshold value) using a model that accounted variances due to lactation stage, calving season, age at calving, breeding region, parity, permanent environment, interaction between hear and year, and individual animal. The estimated high genetic correlations between the daily milk production in normal and heat stress conditions, as well as high correlations among the EBVs in normal and heat stress conditions, point out that Holstein cows with high productivity in normal condition will sustain an alike level of production even in terms of heat stress. These results indicate that the Holstein cows are very well acclimatized to the environmental conditions at dairy farms in Croatia. However, these findings should be taken with caution, given that measurements of microclimate parameters were conducted only once at a milk recording day, so the reliability of such measurements could be questionable. In conclusion, in order to realize a completely unambiguous conclusion, further studies that include multiple daily measurements of microclimatic parameters in the farms facilities are necessary.
Prilikom procjene komponenti varijance te uzgojnih vrijednosti za dnevnu proizvodnju mlijeka krava holstein pasmine u uvjetima toplinskog stresa koji je definiran pri različitim graničnim vrijednostima THI-a (68, 70, i 72) korišteno je ukupno 1.275,713 zapisa na kontrolni dan prikupljenih na 90.159 krava. Temperaturno-humidni indeks (THI) koji je izračunat na osnovu izmjerene temperature i relativne vlage u stajama na dan kontrole mliječnosti, korišten je kao mjera toplinskog stresa. Prilikom statističke analize, dnevna proizvodnja mlijeka uvažena je kao bivariatno svojstvo i to u normalnim uvjetima (ispod THIthreshold vrijednosti) te u uvjetima toplinskog stresa (iznad THIthreshold vrijednosti). Primijenjeni statistički model uvažio je varijabilnost uslijed stadija laktacije, sezone teljenja, dobi pri teljenju, regije uzgoja, pariteta, permanentnog okoliša, interakcije između stada i godine te pojedine životinje. Procijenjene visoke vrijednosti genetske korelacije između dnevne proizvodnje mlijeka u normalnim te u uvjetima toplotnog stresa, kao i vrlo visoke vrijednosti korelacija između procijenjenih uzgojnih vrijednosti za dnevnu proizvodnju mlijeka (EBV) u normalnim i toplinsko stresnim uvjetima indiciraju da će visoko proizvodna grla u normalnim okolišnim uvjetima sličnu razinu proizvodnje održati i u uvjetima toplinskog stresa. Dobiveni rezultati ukazuju na činjenicu da su krave holstein pasmine vrlo dobro aklimatizirane na okolišne uvjete na farmama mliječnih goveda u Hrvatskoj. Međutim, ove rezultate treba uzeti s dozom opreza, obzirom da su mjerenja mikroklimatskih parametara u objektima provođena samo jednom na dan kontrole mliječnosti, tako da pouzdanost tih mjerenja može biti upitna. Zaključno, kako bismo utvrdili potpuno nedvosmislen zaključak, neophodna su daljnja istraživanja u kojima će se provoditi višestruka dnevna mjerenja mikroklimatskih parametara u farmskim objektima.
Bibliografija: 29 jed.
Summary ; Sažetak.
Keywords: Mlijeko -- Proizvodnja mlijeka -- Toplinski stres -- Genetski parametri -- Holstein pasmina